2021
DOI: 10.1002/ece3.7466
|View full text |Cite
|
Sign up to set email alerts
|

Turning to the dark side: LED light at night alters the activity and species composition of a foraging bat assemblage in the northeastern United States

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 66 publications
(116 reference statements)
0
13
1
Order By: Relevance
“…No bat species in our study negatively responded to ALAN. Even though our results do not align with previous studies of ALAN and North American bats [ 24 , 36 ], they could be explained by the possibility that urban-dwelling bats might have adapted to ALAN. Considering that previous studies of North American bats were conducted in areas where ALAN was generally absent, urban bats in our studies were very likely to respond to ALAN differently, which might be another example of urban wildlife adapting to a city life [ 30 , 31 , 32 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…No bat species in our study negatively responded to ALAN. Even though our results do not align with previous studies of ALAN and North American bats [ 24 , 36 ], they could be explained by the possibility that urban-dwelling bats might have adapted to ALAN. Considering that previous studies of North American bats were conducted in areas where ALAN was generally absent, urban bats in our studies were very likely to respond to ALAN differently, which might be another example of urban wildlife adapting to a city life [ 30 , 31 , 32 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Several radio-telemetry or GPS tracking studies have shown avoidance of well-illuminated areas in bat flights [ 18 , 19 , 20 , 21 ]. When experimentally introducing ALAN to naturally unlit environments, ALAN disrupted flight patterns and reduced activity in many species, regardless of the light source types (light-emitting diodes/LED, sodium pressure, or mercury vapor) of ALAN [ 22 , 23 , 24 , 25 , 26 ]. Acoustic studies that focused on ALAN in urban settings also found negative impacts of ALAN on bat commuting activity [ 27 , 28 , 29 ], even though urban bats might have adapted behaviorally to the city [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast [87,88], other research reported increased foraging activity near flood lights for Kuhl's pipistrelle bats (Pipistrellus kuhlii), a species that occurs throughout southern Europe, north Africa, and west Asia, suggesting the perception of light wavelength and/or foraging behavior as potential indicators for light's effect on bat species. Using acoustic monitoring in North America, Seewagen et al [89] concluded that eastern red and hoary bats displayed no significant differences in activity between dark and LED-lit conditions.…”
Section: Lightsmentioning
confidence: 99%
“…Among bats, species composing regional communities often respond in different ways, with both spectral composition and intensity influencing response; few patterns of bat response to ALAN apply to all species [ 80 , 81 ]. In general, experiments consistently demonstrate certain species of bats avoiding experimentally lit areas of landscapes, whereas other species in a local bat community might forage opportunistically on insects at the lights [ 82 , 83 ]. For example, experimental treatment with ALAN reduced drinking by forest bats in Italy [ 84 ], and in an urban area of Germany, greater noctule bats ( Nyctalus noctula ) tended to avoid lit areas but opportunistically foraged in some situations [ 85 ].…”
Section: Discussionmentioning
confidence: 99%